2010
DOI: 10.1111/j.1469-8137.2010.03273.x
|View full text |Cite
|
Sign up to set email alerts
|

A sequence‐tagged genetic map for the brown alga Ectocarpus siliculosus provides large‐scale assembly of the genome sequence

Abstract: Summary Ectocarpus siliculosus has been proposed as a genetic and genomic model for the brown algae and the 214 Mbp genome of this organism has been sequenced. The aim of this project was to obtain a chromosome‐scale view of the genome by constructing a genetic map using microsatellite markers that were designed based on the sequence supercontigs. To map genetic markers, a segregating F2 population was generated from a cross between the sequenced strain (Ec 32) and a compatible strain from northern Chile. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 32 publications
0
88
1
Order By: Relevance
“…Nuclear DNA was amplified in a microsatellite region whose length differs by 40 bp between Ec32 (genetic background of the etl mutant) and Ec568 (Heesch et al, 2010; primer sequences are ESM27F, 59-TGTAAAACGGCCAGTGCAACTGCCCTCG-GAAAATAAG-39, and ESM27R, 59-GCGCGGTCGATGCTAATAATAA-CTA-39). The amplification was performed in an Applied Biosystems thermocycler (35 cycles, 0.5 min 948C, 0.5 min 658C, 1 min 728C) using GoTaq DNA polymerase (Promega).…”
Section: Cross-verificationmentioning
confidence: 99%
“…Nuclear DNA was amplified in a microsatellite region whose length differs by 40 bp between Ec32 (genetic background of the etl mutant) and Ec568 (Heesch et al, 2010; primer sequences are ESM27F, 59-TGTAAAACGGCCAGTGCAACTGCCCTCG-GAAAATAAG-39, and ESM27R, 59-GCGCGGTCGATGCTAATAATAA-CTA-39). The amplification was performed in an Applied Biosystems thermocycler (35 cycles, 0.5 min 948C, 0.5 min 658C, 1 min 728C) using GoTaq DNA polymerase (Promega).…”
Section: Cross-verificationmentioning
confidence: 99%
“…Despite this situation, first reports on the characterization of natural (Peters et al, 2008) and artificial mutants (Coelho et al, 2011;Lebail et al, 2010Lebail et al, , 2011, altered in their development pattern, have been published. The availability of a genetic map generated recently for the Ectocarpus reference strain (Heesch et al, 2010) represents a valuable tool for further genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…isolated from independently micro-dissected unilocular sporangia). Initially, 30 individuals from this segregating population were genotyped with 97 microsatellite markers distributed at ∼30 cM intervals along the length of the entire genetic map (Heesch et al, 2010). Additional microsatellite markers were developed based on the Ec32 genome sequence to fine map the mutant locus (Table S1).…”
Section: Genetic Mapping Of the Imm Locusmentioning
confidence: 99%
“…Peters et al (2008) showed that the imm mutation behaved as a recessive, Mendelian allele and was located on an autosome. To map this mutation, a backcrossed descendant of strain Ec137 carrying the imm mutation (Peters et al, 2008) was crossed with the outcrossing line Ec568 (Heesch et al, 2010) to generate a segregating family of 1699 haploid progeny. The IMM locus was then mapped genetically by scanning the genome for linked microsatellite markers and fine mapping the mutation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation